2000
DOI: 10.1007/s004050050212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aromatic DNA adducts in laryngeal biopsies

Abstract: Epidemiological studies have confirmed the correlation between tobacco smoking, environmental pollution and the incidence of cancers of the respiratory tract. The occurrence of laryngeal cancer in Poland is relatively high compared to other European countries. Since 1969 the mortality related to larynx cancer appears to be increasing. Tobacco smoke contains an abundance of such carcinogenic compounds as polycyclic aromatic hydrocarbons (PAH), aromatic amines and N-nitrosoamines, which can react with DNA and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Consistent with what we have previously reported (7,8), adduct levels were higher in nontumor cells compared with tumor cells. Several studies of other tissues that measured PAH-DNA adducts in both tumor and adjacent nontumor cells, including lung (38), laryngeal (39), pancreas (40), and liver (41), have also reported higher Research.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with what we have previously reported (7,8), adduct levels were higher in nontumor cells compared with tumor cells. Several studies of other tissues that measured PAH-DNA adducts in both tumor and adjacent nontumor cells, including lung (38), laryngeal (39), pancreas (40), and liver (41), have also reported higher Research.…”
Section: Discussionmentioning
confidence: 98%
“…It is significant, therefore, that it is still somewhat unclear which measures of tobacco smoke exposure are most highly correlated with smoking related DNA adduct levels. Several studies now support the idea that current smokers have higher adduct levels compared with former smokers, and that daily cigarette consumption (cigarettes per day) is the most predictive measure of variations in adduct levels in target (Wiencke et al, 1999;Szyfter et al, 1999a;Banaszewski et al, 2000;Romano et al, 1999) and surrogate tissues of current smokers Hou et al, 2001). In one study the daily cigarette tar consumed, but not the number of cigarettes, was found to be predictive of adduct levels in blood MNCs (Godschalk et al, 1998).…”
Section: Dna-adducts and Exposure To Lung Carcinogensmentioning
confidence: 98%
“…A series of studies have shown that smoking is associated with smoking related adducts in the oral cavity and larynx (Banaszewski et al, 2000;Szyfter et al, 1999a,b;Nath et al, 1998). In a casecontrol study, induced DNA adduct levels were found to be associated with risk of head and neck cancer (Li et al, 2001a).…”
Section: Dna Adducts Associated With Lung Cancermentioning
confidence: 99%
“…Aromatic DNA adducts could be localised in laryngeal biopsies of patients suffering from primary laryngeal carcinomas, with remarkable individual differences. Nevertheless, adduct levels were found to correlate with age, cigarette smoking and TNM gradings of tumours (Banaszewski et al 2000). The causal connection of laryngeal DNA adducts with PAH from tobacco smoke was considered very likely (Degawa et al 1994;Badawi et al 1996).…”
Section: Discussionmentioning
confidence: 97%